Evaluation of Citizen Science Project on Birdwatching in Germany: Advantages and Limits - Andrea Ehrmann; Oliver Tillmanns (Diversity)
Since 2005, The Nature and Biodiversity Conservation Union (NABU, Germany) has called upon people in Germany to count birds in their gardens during a defined time (Friday to Sunday) in May. This “Stunde der Gartenvögel” (hour of the garden birds) aims at obtaining a yearly overview of the birds in villages and towns. While this birdwatching action gives a broad overview due to the large number of gardens and parks involved (around 40,000 in the year 2024), several drawbacks must be mentioned that may impede the comparability of the counted bird numbers from one year to another. Here we give an overview of the chronological development of the overall numbers of species and specifically of the most frequent garden birds. We discuss correlations with external factors, such as weather and numbers of participants, and compare the results with ornithological studies in the same period as well as with the results of the yearly Birdrace in Germany, where ornithologically interested people count birds in a defined area on the full first Saturday in May. The main drawback of the citizen science project was found to be misidentifications of birds, especially evident in the case of the Tree Sparrow, combined with birds not being recorded because they could not be identified. The main advantage, on the other hand, is the large amount of data from the “Stunde der Gartenvögel”, which is important for measuring especially the trends of well-known, frequent species much better than the Birdrace. Ideally, all data taken in different ways should be combined, and misinterpretations should be reduced by showing male and female birds of species with strong gender dimorphism.